2008
DOI: 10.1037/a0012748
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory insular cortex lesions disrupt drug-induced, but not lithium chloride-induced, suppression of conditioned stimulus intake.

Abstract: Rats suppress intake of a normally preferred 0.15% saccharin conditioned stimulus (CS) when it is paired with an aversive agent like lithium chloride (LiCl) or a preferred substances such as sucrose or a drug of abuse. The reward comparison hypothesis suggests that rats avoid intake of a saccharin cue following pairings with a drug of abuse because the rats are anticipating the availability of the rewarding properties of the drug. The present study used bilateral ibotenic acid lesions to examine the role of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 123 publications
8
50
0
1
Order By: Relevance
“…Other data demonstrate that these subregions project directly to the ventral edge of primary somatosensory cortex in the same modality specific order [38, 44]. This proves the area we damaged not only contains neurons that respond to gustatory and lingual somatosensory stimuli, but also that these cells form one limb of a classic thalamocortical circuit [45]. …”
Section: Discussionsupporting
confidence: 54%
“…Other data demonstrate that these subregions project directly to the ventral edge of primary somatosensory cortex in the same modality specific order [38, 44]. This proves the area we damaged not only contains neurons that respond to gustatory and lingual somatosensory stimuli, but also that these cells form one limb of a classic thalamocortical circuit [45]. …”
Section: Discussionsupporting
confidence: 54%
“…This demonstrates that the thalamic lesions did affect at least one taste-guided behavior. In prior experiments using similar procedures, somewhat more medial thalamic damage as well as lesions of gustatory cortex disrupted suppression of a taste CS when it was paired with either a highly preferred drug or sucrose [3840]. The third paper in this series, then, uses sham feeding of sucrose and corn oil to test whether the PBN or TOA lesion will disrupt comparison of the relative value of different stimulus concentrations in an anticipatory contrast paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis anticipates that IC lesions should delay but not prevent the acquisition of drug-induced CS suppression. Interestingly, Geddes, Han, Baldwin, Norgren and Grigson (2008; Experiment 1) recently reported that ICX rats required twice as many CS-US pairings as SHAM subjects (6 versus 3 trials, respectively) for a cocaine US (10 mg/kg) to suppress intake of a Polycose CS3. Furthermore, Roman and Reilly (2009), in a study showing that IC lesions disrupt morphine-induced saccharin suppression, provided some evidence, albeit between-phase rather than across-groups, that latent inhibition influences drug-induced CS suppression in neurologically intact rats.…”
Section: Discussionmentioning
confidence: 99%